The actor-partner interdependence mediation model of infertility-related stress and subjective happiness in infertile couples: the mediating role of dyadic coping - Eun Jin Kim; Ju-Hee Nho (Journal of Korean Academy of Nursing, 2026)
Purpose: This study aimed to identify the mediating effect of dyadic coping and the actor–partner effects of infertility-related stress, dyadic coping, and subjective happiness among infertile couples by applying the actor–partner interdependence mediation model.Methods: A total of 115 infertile couples, comprising women diagnosed with primary infertility and their spouses, participated in an online survey. Data were collected between November 17, 2022 and January 9, 2023, and analyzed using IBM SPSS Statistics version 25.0 and SmartPLS version 4.0.9.2 with the path weighting scheme. Bootstrapping with 5,000 resamples was performed to estimate 95% confidence intervals.Results: Significant correlations were observed between infertile women and their spouses in infertility-related stress, dyadic coping, and subjective happiness, indicating mutual psychological influence within couples. Infertility-related stress in both women and spouses had actor effects on their own dyadic coping and subjective happiness. Women’s dyadic coping had an actor effect on their own subjective happiness, whereas spouses’ dyadic coping had a partner effect on women’s subjective happiness. Among women with infertility, dyadic coping significantly mediated the association between infertility-related stress and subjective happiness. A significant partner-mediated effect was also observed for women’s subjective happiness, whereas no significant mediating effect was found for spouses’ own subjective happiness.Conclusion: Infertility-related stress was associated with subjective happiness through dyadic coping among women with infertility. In addition, spouses’ infertility-related stress was indirectly associated with women’s subjective happiness through spouses’ dyadic coping. These findings suggest that interventions designed to strengthen dyadic coping may help reduce infertility-related stress and improve subjective happiness among infertile couples.